Candidates for the Priesthood in Poland A.D. 2020: A Research Report - Pawlina, Krzysztof (Verbum Vitae, 2021)
The article essentially aims at answering who were the Polish young men wishing to become priests in 2020 as compared with the candidates who entered Polish seminaries in 2000. The answer was based on quantitative and qualitative surveys conducted in 2000 and 2019 among seminarians at the very beginning of their priestly formation. The questionnaires, though exposing great cognitive possibilities, cannot measure what concerns the mystery of vocation or faith. Despite these limitations, the obtained results have allowed us to find out, for example, where the seminarians came from and what their backgrounds were. They also show their interests, the level of their general and religious knowledge as well as their values. Of importance was to get to know their visions of the priesthood and the Church. The present paper, as a synthesis of the study published in book form, gives a profile of the contemporary candidate for the priesthood. The results of the research can be used by formators and all those who make arrangements for the introduction of the new Ratio Institutionis in Poland.